A boundary element-vortex particle hybrid method with inviscid shedding scheme. (30th May 2018) - Wang, Youjiang; Abdel-Maksoud, Moustafa; Song, Baowei
Highlights: Converting one constant-strength dipole panel to multiple vortex particles. Determine inter-particle spacing according to the boundary layer thickness. Both steady and oscillating hydrofoils are modelled. The convergence with regard to panel size and time step is investigated. Abstract: This work presents a hybrid method combining the low order boundary element method and the vortex particle method, in the sense that inviscid wake panels are shed from the trailing edge and then converted to vortex particles for viscous simulation of the slipstream flow. The way to combine these two solution techniques are described in detail as well as the methodology to convert wake panels to vortex particles. Two elliptical hydrofoils in the steady flow and an oscillating rectangular hydrofoil are investigated with the hybrid method. It is demonstrated that, to obtain a physical vorticity distribution, the inter-particle spacing cannot be chose arbitrarily, but should be correlated to the boundary layer thickness. The hybrid method shows a good capability to conserve the axial vorticity. The obtained tangential velocity profile across the tip vortex also exhibits an acceptable correlation with experimental measurement. Also presented are the obtained hydrodynamic forces, their convergence with regards to panel size and time step, and the comparison with results of RANS solver and boundary element method.